Preparation method of high-conductivity PEDOT three-dimensional micro-nano structure
Patent Information
- Application Number
- CN202511928115.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-19
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-12-19
AI Technical Summary
然而,这一热处理过程会引入新的问题:高温环境极易导致已成型精密的微纳结构发生收缩、熔融或塌陷等形貌恶化,使得制备复杂的三维构型变得异常困难甚至不可能
[0014]本发明技术效果:本发明公开了一种高电导PEDOT三维微纳结构制备方法,能够有效提升所制备三维微纳结构的导电性能,并实现电导率在较宽范围内的灵活调控。本发明简化了制备流程,避免了传统工艺中必需的后续热处理环节,从而缩短了生产周期并降低了因高温导致的微纳结构形貌损坏风险,使得复杂三维构型的制备成为可能。本发明通过优化材料体系与工艺参数,提高了加工效率与结构成型的重复性,保证了不同批次产品性能的一致性与稳定性。同时,本发明所获得的微纳结构具有高分辨率与良好的结构完整性,其与基底的结合牢固,能够满足微型电学器件及生物神经接口等领域对高性能三维导电元件的应用需求。
Smart Images

Figure CN121672414B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of micro-nano manufacturing technology, and in particular relates to a method for preparing a high-conductivity PEDOT three-dimensional micro-nano structure. Background Technology
[0002] Three-dimensional conductive micro / nanostructures are core components in cutting-edge fields such as microelectronic devices, flexible electronic sensors, and biological neural interfaces. Their performance directly determines the signal transmission efficiency, response sensitivity, and integration density of these devices. As electronic devices continue to evolve towards miniaturization, integration, and three-dimensionality, the market demand for three-dimensional conductive micro / nanostructures with high resolution, high conductivity, and precisely tunable morphology is becoming increasingly urgent. Two-photon polymerization technology, with its high resolution below 250 nm and true three-dimensional additive manufacturing capabilities, has become a key technological path for fabricating such micro / nanostructures. Poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate, as a commonly used conductive polymer, is widely used to construct polymer-based conductive micro / nanostructures due to its good biocompatibility and environmental stability. However, this material system itself has inherent limitations, restricting its application in high-performance devices.
[0003] Currently, there are two main types of methods for fabricating PEDOT-based conductive structures using two-photon polymerization. The first type is the pure polymer-based method, which involves directly mixing PEDOT:PSS with photoresist components and then processing them. For example, existing techniques have used this method to fabricate conductive microstructures, but the conductivity of the resulting structures is generally low, reaching a maximum of only about 2.7 × 10⁻⁶. 4 The S / m ratio is insufficient to meet the stringent requirements of many micro-electronic devices for low resistance and high current carrying capacity. More importantly, the PEDOT:PSS in this scheme is prone to uneven dispersion, resulting in defects in the conductive path and unstable conductivity values. Furthermore, it is difficult to achieve precise and reliable control near the required performance benchmark simply by adjusting the PEDOT:PSS content.
[0004] The second approach attempts to improve conductivity by doping with fillers such as multi-walled carbon nanotubes or metal particles. For example, some studies have used solution post-treatment to dope multi-walled carbon nanotubes into PEDOT hydrogels. However, this method suffers from difficulties in precisely controlling the filler loading and uneven solution diffusion, resulting in poor consistency in conductivity and low yield of the prepared structures. Another common approach is to dope with metal particles and then densify the metal network through subsequent heat treatment to improve conductivity. However, this heat treatment process introduces new problems: high-temperature environments can easily cause the already formed, precise micro / nanostructures to shrink, melt, or collapse, leading to morphological deterioration and making the preparation of complex three-dimensional configurations extremely difficult or even impossible. Furthermore, the additional heat treatment step not only significantly prolongs the preparation cycle but also increases process complexity and energy costs. In addition, processes relying on large-scale doping with precious metals or using two-photon reduction of metals suffer from high raw material costs and slow processing speeds. Therefore, developing a method for preparing three-dimensional conductive micro / nanostructures that requires no post-heat treatment and simultaneously achieves high conductivity, high shape fidelity, high processing efficiency, and good economics has become a pressing technical challenge in this field. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention proposes a method for fabricating high-conductivity PEDOT three-dimensional micro / nano structures. By optimizing the conductive pathway through the synergistic effect of metal nanoparticles and PSS, and without the need for subsequent heat treatment, this method achieves efficient fabrication of high-conductivity, structurally complete three-dimensional conductive micro / nano structures, which is applicable to fields such as micro-electrical devices and biological neural interfaces.
[0006] To achieve the above objectives, this invention provides a method for fabricating high-conductivity PEDOT three-dimensional micro / nano structures, comprising: We provide composite photoresists comprising polymer monomers, conductive polymer PEDOT:PSS, metal nanoparticles, and photoinitiators; Pretreatment of the substrate enhances its surface activity and binding capacity; The composite photoresist is coated onto the pretreated substrate; A femtosecond laser is used to induce a two-photon polymerization reaction in the composite photoresist, forming a three-dimensional micro / nano structure prototype on the substrate. The prototype of the three-dimensional micro / nano structure is developed to obtain the final three-dimensional micro / nano structure.
[0007] Optionally, the composite photoresist comprises acrylate compounds as polymer monomers, PEDOT:PSS as conductive base filler, metal nanoparticles as conductive modulating filler, and photoinitiators with absorption peaks in the range of 250-320 nm.
[0008] Optionally, the metal nanoparticles are metal nanoparticles that can form coordination bonds with the PSS segments in PEDOT:PSS, and the average particle size of the metal nanoparticles is 15-25 nm, and their polydispersity index (PDI) is less than or equal to 0.25.
[0009] Optionally, the pretreatment process for the substrate includes: first, cleaning the substrate with oxygen plasma, and then silanizing the cleaned substrate with a silane coupling agent containing functional groups that can react with the polymer monomers.
[0010] Optionally, the process of initiating two-photon polymerization using a femtosecond laser is carried out under the condition that the sample thickness is 8-12 μm, the wavelength of the femtosecond laser is 500-600 nm, the pulse width is 100-300 fs, and the scanning speed is 5-50 μm / s.
[0011] Optionally, the development process includes: sequentially immersing the three-dimensional micro / nano structure prototype in water and an organic solvent in a stepwise manner, followed by drying.
[0012] Optionally, the photoinitiator is Irgacure 2959, Irgacure 184, or Darocur 1173.
[0013] Optionally, the acrylate compound is polyethylene glycol diacrylate or trimethylolpropane triacrylate.
[0014] Technical advantages of this invention: This invention discloses a method for fabricating high-conductivity PEDOT three-dimensional micro / nano structures, which can effectively improve the conductivity of the fabricated three-dimensional micro / nano structures and achieve flexible control of conductivity over a wide range. This invention simplifies the fabrication process, avoiding the necessary subsequent heat treatment step in traditional processes, thereby shortening the production cycle and reducing the risk of micro / nano structure morphology damage due to high temperatures, making the fabrication of complex three-dimensional configurations possible. This invention improves processing efficiency and the repeatability of structure forming by optimizing the material system and process parameters, ensuring the consistency and stability of performance across different batches of products. Simultaneously, the micro / nano structures obtained by this invention have high resolution and good structural integrity, and their bonding with the substrate is strong, meeting the application requirements of high-performance three-dimensional conductive components in fields such as micro-electronic devices and biological neural interfaces. Attached Figure Description
[0015] The accompanying drawings, which form part of this application, are used to provide a further understanding of this application. The illustrative embodiments and descriptions of this application are used to explain this application and do not constitute an undue limitation of this application. In the drawings: Figure 1 This is a schematic diagram illustrating the components and functions of the composite photoresist system in an embodiment of the present invention; Figure 2 This is a schematic diagram of the particle size distribution of gold nanoparticles in an embodiment of the present invention; Figure 3 This is a schematic diagram comparing the effects of substrate pretreatment processes in embodiments of the present invention; Figure 4 This is a schematic diagram of the two-photon polymerization processing system according to an embodiment of the present invention; Figure 5 This is a SEM image of the two-dimensional conductive micro / nanowire structure according to an embodiment of the present invention; Figure 6 This is a bright-field optical microscope image of the two-dimensional conductive micro / nanowire structure according to an embodiment of the present invention. Figure 7 This is a graph showing the relationship between AuNPs concentration and conductivity in an embodiment of the present invention. Figure 8 Scanning electron microscope images of a high-conductivity PEDOT three-dimensional wood stack structure were prepared for an embodiment of the present invention. Detailed Implementation
[0016] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. This application will now be described in detail with reference to the accompanying drawings and embodiments.
[0017] It should be noted that the steps shown in the flowchart in the accompanying drawings can be executed in a computer system such as a set of computer-executable instructions, and although a logical order is shown in the flowchart, in some cases the steps shown or described may be executed in a different order than that shown here.
[0018] PEDOT:PSS: Poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate), a commonly used conductive polymer, serves as the basic conductive component of the conductive micro / nano structure in this invention, achieving high conductivity through synergistic interaction with metal nanoparticles.
[0019] PEGDA: Polyethylene glycol diacrylate, as a polymer monomer for photoresist, provides a molding basis for micro and nano structures. In this invention, the preferred type is a molecular weight of 700 with a mass fraction of 40~45wt%.
[0020] Irgacure 2959: 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone, an ultraviolet photoinitiator with an absorption peak in the range of 250-320 nm, suitable for two-photon polymerization reactions. It can also be replaced by other photoinitiators with the same absorption peak range (such as Irgacure 184, Darocur 1173, etc.).
[0021] AuNPs (gold nanoparticles): In this invention, it specifically refers to gold nanoparticles with an average particle size of 15~25nm and a polydispersity index (PDI) ≤0.25. The conductive pathway is optimized by forming Au-S bonds with PSS segments. It can also be replaced by silver nanoparticles, platinum nanoparticles, or other metal nanoparticles that can form coordination bonds with PSS.
[0022] PDI (Polydispersity Index): Used to characterize the uniformity of particle size distribution of nanoparticles; the smaller the value, the more concentrated the particle size distribution. In this invention, the PDI of the metal nanoparticles is ≤0.25, ensuring uniform dispersion of the particles in the photoresist and guaranteeing the stability of conductivity.
[0023] Two-photon polymerization: a micro-nano 3D printing technology based on femtosecond lasers, with high resolution (<100nm) and true three-dimensional additive manufacturing capabilities. In this invention, metal nanoparticle doping and process optimization are combined to realize the preparation of complex three-dimensional conductive micro-nano structures (such as three-dimensional wood stacking structures).
[0024] Dynamic light scattering (DLS): a technique for analyzing particle size and distribution by detecting fluctuations in the intensity of scattered light over time. In this invention, it is used to determine the average particle size (15~25nm) and polydispersity index (PDI≤0.25) of metal nanoparticles.
[0025] Dual-probe IV testing: a method for calculating the conductivity of a material by applying voltage and measuring current through two probes. In this invention, it is used to quantify the conductivity (e.g., 2.8 × 10⁻⁶) of high-conductivity PEDOT three-dimensional micro / nano structures. 4 S / m).
[0026] KH-570 (Methacryloxysilane): A silane coupling agent containing a methacryloyloxy group, which can chemically react with PEGDA in photoresist to form chemical bonds, thereby improving the adhesion strength between the photoresist and the substrate. It can also be replaced by a silane coupling agent containing vinyl groups or other groups that can react with polymer monomers (such as KH-560).
[0027] Femtosecond laser: pulse width in femtoseconds (10^6) -15 The femtosecond laser in this invention has parameters of wavelength 500~600nm, pulse width 10~100fs, repetition frequency 50~100MHz, and peak power 1~10kW, and is the core equipment for realizing high-resolution processing of two-photon polymerization.
[0028] This embodiment provides a method for fabricating a high-conductivity PEDOT three-dimensional micro / nano structure, including: We provide composite photoresists comprising polymer monomers, conductive polymer PEDOT:PSS, metal nanoparticles, and photoinitiators; Pretreatment of the substrate enhances its surface activity and binding capacity; The composite photoresist is coated onto the pretreated substrate; A femtosecond laser is used to induce a two-photon polymerization reaction in the composite photoresist, forming a three-dimensional micro / nano structure prototype on the substrate. The prototype of the three-dimensional micro / nano structure is developed to obtain the final three-dimensional micro / nano structure.
[0029] Furthermore, the composite photoresist comprises acrylate compounds as polymer monomers, PEDOT:PSS as a conductive base filler, metal nanoparticles as conductive modulating fillers, and photoinitiators with absorption peaks in the range of 250-320 nm.
[0030] Specifically, the implementation process of this embodiment includes: Design and fabrication of composite photoresist systems: Design logic: The core is "polymer monomers provide mechanical support, conductive basic fillers construct pathways, and conductive control fillers optimize performance", taking into account both moldability and conductivity; Component selection: Polymer monomers: acrylates (such as PEGDA) are selected, with a mass fraction of 40~45wt% (to ensure that the structure does not shrink and the mechanical strength meets the requirements); Conductive base filler: PEDOT:PSS, mass fraction 0.4~0.8wt% (close to the dispersion limit to avoid agglomeration affecting conductivity); Conductivity-regulating fillers: metal nanoparticles (such as AuNPs), concentration 0~100 mg / L (optimizing the conductivity pathway through coordination bonds with PSS). Photoinitiator: Type with UV absorption peak of 250~320nm (e.g., Irgacure 2959), mass fraction 1.5~2.5wt% (suitable for two-photon polymerization); Preparation logic: Mix the components according to the ratio, and achieve uniform dispersion by stirring / ultrasound to ensure the stability of the photoresist system.
[0031] Furthermore, the metal nanoparticles are metal nanoparticles that can form coordination bonds with the PSS segments in PEDOT:PSS, and the average particle size of the metal nanoparticles is 15-25 nm, with a polydispersity index (PDI) less than or equal to 0.25.
[0032] Furthermore, the pretreatment process for the substrate includes: first, cleaning the substrate with oxygen plasma, and then silanizing the cleaned substrate with a silane coupling agent containing functional groups that can react with the polymer monomers.
[0033] Specifically, the implementation process of this embodiment includes: Substrate pretreatment process: Problem: In existing technologies, the photoresist has poor adhesion to the substrate, leading to structural detachment; Process design: The combination of "oxygen plasma cleaning (2~4 min) + silanization treatment" is adopted - the former removes substrate impurities and improves activity, while the latter enhances adhesion through chemical bonding (reaction of methacryloyloxy groups with PEGDA); Key requirement: The silane coupling agent must contain a group that reacts with the photoresist monomer (such as the methacryloyloxy group of KH-570).
[0034] Furthermore, the process of initiating two-photon polymerization using a femtosecond laser was carried out under the condition of a sample thickness of 8-12 μm. The femtosecond laser used had a wavelength of 500-600 nm, a pulse width of 100-300 fs, and a scanning speed of 5-50 μm / s.
[0035] Specifically, the implementation process of this embodiment includes: Two-photon polymerization processing: Core objective: To ensure high resolution (<250nm) and structural integrity (no deformation); Parameter design logic: Sample thickness 8~12μm (to reduce aberrations caused by refractive index mismatch); Femtosecond laser parameters (wavelength 500~600nm, pulse width 100-300fs, repetition rate 60~100MHz, peak power 1~10kW, entrance pupil power 1~4mW), scanning speed 5~50μm / s (matching the polymerization reaction rate to avoid ablation due to excessive power / incomplete curing due to insufficient power); Processing compensation amount -0.3~0μm (compensates for aberrations and ensures the focusing accuracy of the light spot).
[0036] Furthermore, the development process includes: sequentially immersing the three-dimensional micro / nano structure prototype in water and organic solvent in stages, followed by drying.
[0037] Specifically, the implementation process of this embodiment includes: Post-processing: Core requirements: Remove uncured photoresist (to ensure structural purity) and prevent structural deformation; General method: Use "water + organic mixed solvent (such as acetone-isopropanol)" for stepwise development (2-4 min each), and air dry or dry at low temperature (avoid high temperature damage to the structure).
[0038] Furthermore, the photoinitiator is Irgacure 2959, Irgacure 184, or Darocur 1173.
[0039] Specifically, the implementation process of this embodiment includes: Photoinitiator replacement: Irgacure 2959 can be replaced with other UV photoinitiators with the same or similar absorption peak range (250-320nm), such as Irgacure 184, Darocur 1173, etc. As long as they can efficiently initiate two-photon polymerization reactions, similar structural forming effects can be achieved.
[0040] Furthermore, the acrylate compound is polyethylene glycol diacrylate or trimethylolpropane triacrylate.
[0041] Specifically, the implementation process of this embodiment includes: Polymer monomer substitution: PEGDA (Mw700) can be replaced by other acrylate monomers with a molecular weight range of 600~1000, such as polyethylene glycol dimethacrylate, trimethylolpropane triacrylate, etc., as long as they can provide sufficient mechanical strength and ensure structural formability, they can be used as substitutes.
[0042] The core components of the composite photoresist system consist of: water-soluble acrylate monomers (such as polyethylene glycol diacrylate, trimethylolpropane triacrylate, etc.) as polymer monomers (mass fraction 40~45wt%), PEDOT:PSS as conductive base filler (mass fraction 0.4~0.8wt%), metal nanoparticles that can form coordination bonds with PSS (such as gold nanoparticles, silver nanoparticles, etc., average particle size 15~25nm, PDI≤0.25) as conductive control filler (concentration 0~100mg / L), and photoinitiators with ultraviolet absorption peaks of 250~320nm (such as Irgacure series, Darocur series, etc.) as polymerization initiators (mass fraction 0.5~2wt%), supplemented by solvents to form a five-component composite photoresist system. Through the synergistic effect of each component, this system ensures both the mechanical formability of micro and nanostructures and achieves high conductivity and wide-range controllability. The core protection lies in the "combination of component types + ratio range", rather than a single formulation parameter.
[0043] Replacement of conductive modulators: Gold nanoparticles can be replaced with other high-conductivity metal nanoparticles that can form coordination bonds with PSS, such as silver nanoparticles and platinum nanoparticles. These metal nanoparticles can also induce changes in the spatial arrangement of PSS segments, optimize the PEDOT conductive pathway, and achieve conductivity enhancement and regulation.
[0044] like Figure 1 The diagram shows the components and functions of the composite photoresist system. Figure 1The composition of PEGDA, PEDOT:PSS, AuNPs, Irgacure 2959, and ultrapure water was demonstrated, and the functional roles of each component were clarified. PEGDA provides the molding basis for the polymer monomer, PEDOT:PSS is the conductive basic filler, AuNPs is the conductive regulating filler, Irgacure 2959 is the photoinitiator, and ultrapure water is the solvent. At the same time, the interaction between AuNPs and PSS segments was demonstrated, that is, AuNPs induce changes in the spatial arrangement of PSS segments through Au-S bonds, thereby optimizing the PEDOT conductive pathway.
[0045] like Figure 2 The figure shows the particle size distribution of gold nanoparticles. This figure represents the results of dynamic light scattering tests. The horizontal axis represents the particle size (nm), and the vertical axis represents the percentage of particle size distribution (%). The test shows that the average particle size of the gold nanoparticles is 19.53 nm, the PDI is 0.226, and the particle size distribution is concentrated in the range of 15~25 nm, indicating that the prepared gold nanoparticles are uniformly dispersed and meet the requirements for use in composite photoresists.
[0046] like Figure 3 The figure shows a comparison of the effects of substrate pretreatment processes. It illustrates the adhesion effects of three different substrate treatment methods: untreated, oxygen plasma cleaning only, and oxygen plasma cleaning + silanization. The figure shows that the photoresist on the untreated substrate surface is easily detached, the adhesion of the substrate treated with oxygen plasma cleaning only is average, while the photoresist on the substrate treated with oxygen plasma cleaning + silanization is tightly bonded to the substrate with no detachment, verifying the effectiveness of this pretreatment process.
[0047] like Figure 4 The diagram shows a schematic of a two-photon polymerization processing system. It illustrates the components of a femtosecond laser micro / nano 3D structure printing system, including a laser processing section and an imaging section. The laser processing section consists of a femtosecond laser, beam splitter, lens, pinhole, optical switch, objective lens, and nanoscale piezoelectric displacement stage, used to generate and control the laser beam for polymerization processing. The imaging section consists of an illumination lamp, filter, field lens, and camera, used for real-time observation of the processing. All components work together to achieve precise fabrication of three-dimensional micro / nano structures.
[0048] like Figure 5 The image shows a SEM image of a two-dimensional conductive micro / nanowire structure. This image is a scanning electron microscope (SEM) image of a two-dimensional conductive micro / nanowire structure fabricated on a glass slide. As can be seen from the image, the structure has clear lines, neat edges, and no defects such as burrs or breaks, indicating high fabrication precision and good structural integrity.
[0049] like Figure 6The image shows a bright-field optical microscope image of a two-dimensional conductive micro / nanowire structure. This image, fabricated on a gold electrode, demonstrates the connection between the structure and the electrode. The structure and electrode have good contact with each other, with no obvious gaps, providing a solid foundation for subsequent electrical performance testing.
[0050] like Figure 7 The graph shows the relationship between AuNPs concentration and conductivity. The horizontal axis represents the concentration of gold nanoparticles (mg / L), and the vertical axis represents the conductivity (×10⁻⁶). 4 With a fixed PEDOT:PSS content of 0.6 wt%, as the AuNPs concentration increased from 0 mg / L to 40 mg / L, the conductivity increased from 1.4 × 10⁻⁶ m / s. 4 S / m increased to 8.5×10 4 The conductivity increased by 489.32% (S / m); when the AuNPs concentration exceeded 40 mg / L, the conductivity gradually decreased, indicating that the conductivity could be maintained between 2.1 × 10³ and 8.5 × 10³ by adjusting the AuNPs concentration. 4 Precise control within the S / m range.
[0051] like Figure 8 The image shows a scanning electron microscope image of the fabricated high-conductivity PEDOT three-dimensional wood-stacking structure. This image illustrates the three-dimensional wood-stacking conductive micro / nanostructure fabricated using the method of this invention. It comprises multiple interconnected three-dimensional units, exhibiting a regular stacked configuration. The unit surfaces have clear textures, neat edges, and no obvious deformation or defects. This image verifies that the method of this invention can achieve the fabrication of high-conductivity PEDOT micro / nanostructures with complex three-dimensional configurations, and that the structural integrity and molding accuracy meet the design requirements.
[0052] An application example of this invention is as follows: This embodiment uses "preparing a material with an electrical conductivity of 8.5 × 10⁻⁶" as an example. 4 Taking the "high conductivity PEDOT two-dimensional line structure with S / m" as an example, the feasibility of the technical solution is verified. The specific operation steps are as follows: (1) Preparation of aqueous dispersion of gold nanoparticles: According to the Turkevitch synthesis method: the molar ratio of chloroauric acid to sodium citrate is 1:3. Take 2 mL of 1 mM chloroauric acid solution, heat it to 100°C, and under magnetic stirring at 1000 rpm, quickly add 176.4 μL of 34 mM sodium citrate solution. React for 3 min until the solution turns wine red, and then cool to room temperature. Purification and concentration: Centrifuge at 7000 rpm for 20 min, remove supernatant to a concentration of 1091.51 mg / L. Dynamic light scattering test: average particle size 19.53 nm, PDI=0.226, recovery rate 75.59% (meets the requirements of "particle size 15~25 nm, recovery rate ≥70%" in the technical solution).
[0053] (2) Preparation of composite photoresist: Weigh the following by mass fraction: PEGDA (Mw700) 41.8wt%, PEDOT:PSS 0.6wt%, Irgacure 2959 2.0wt%. Add gold nanoparticle concentrate to make the AuNPs concentration 40mg / L (the optimal value within the range of "0~100mg / L" in the technical solution), and make up to 100wt% with ultrapure water. The composite photoresist was magnetically stirred at 1500 rpm for 2 hours to obtain a uniform and transparent composite photoresist (to verify the requirement of "uniform dispersion" in the technical solution).
[0054] (3) Substrate pretreatment: The glass substrate is cleaned with oxygen plasma for 3 minutes (within the range of "2~4 minutes" in the technical solution); Prepare a silane coupling agent mixture: 2 mL ethanol + 6 mL glacial acetic acid diluted 1:9 + 0.1 mL KH-570, add 100 μL to the substrate surface, let stand for 5 min, rinse with ethanol and air dry (to verify the "chemical bonding enhances adhesion" scheme).
[0055] (4) Two-photon polymerization processing: Sample assembly: Fix the sample according to the sequence of "glass slide - glass slide with grid electrode - ultra-thin tape - glass slide", and coat it with photoresist to control the thickness to 10μm (within the range of "8~12μm" in the technical solution). Equipment parameters: laser wavelength 560nm, repetition frequency 80MHz, processing compensation -0.2μm, power 2mW, scanning speed 10μm / s, processed according to the two-dimensional line structure parameters of "inter-electrode line length 30μm".
[0056] (5) Post-processing and performance testing: Developing: Soak in ultrapure water for 3 minutes → Soak in acetone-isopropanol (1:5) for 3 minutes, then air dry; Performance testing: Dual-probe IV test, calculated according to σ=L / (R·A), conductivity is 8.5×10 4 S / m (verifying the "high conductivity" target of the technical solution), no structural detachment or shrinkage (verifying substrate adhesion and structural integrity).
[0057] This embodiment optimizes the conductive pathway of PEDOT by doping with gold nanoparticles, significantly improving the structural conductivity; the use of "oxygen plasma cleaning + silanization treatment" improves substrate adhesion and ensures the repeatability of structure preparation; optimized processing parameters reduce the influence of aberrations and ensure high resolution; the absence of heat treatment simplifies the process and reduces costs; and the scanning speed reaches over 10 μm / s, improving processing efficiency.
[0058] This invention discloses a method for fabricating high-conductivity PEDOT three-dimensional micro / nanostructures, which effectively improves the conductivity of the fabricated three-dimensional micro / nanostructures and allows for flexible control of conductivity over a wide range. This invention simplifies the fabrication process, avoiding the necessary subsequent heat treatment step in traditional processes, thereby shortening the production cycle and reducing the risk of micro / nanostructure morphology damage due to high temperatures, making the fabrication of complex three-dimensional configurations possible. By optimizing the material system and process parameters, this invention improves processing efficiency and the repeatability of structure forming, ensuring the consistency and stability of performance across different batches of products. Furthermore, the micro / nanostructures obtained by this invention possess high resolution and good structural integrity, exhibiting strong adhesion to the substrate, and can meet the application requirements of high-performance three-dimensional conductive components in fields such as micro-electronic devices and biological neural interfaces.
[0059] The above are merely preferred embodiments of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.
Claims
1. A method for fabricating a high-conductivity PEDOT three-dimensional micro / nano structure, characterized in that, include: We provide composite photoresists comprising polymer monomers, conductive polymer PEDOT:PSS, metal nanoparticles, and photoinitiators; Pretreatment of the substrate enhances its surface activity and binding capacity; The composite photoresist is coated onto the pretreated substrate; A femtosecond laser is used to induce a two-photon polymerization reaction in the composite photoresist, forming a three-dimensional micro / nano structure prototype on the substrate. The prototype of the three-dimensional micro / nano structure is developed to obtain the final three-dimensional micro / nano structure. The metal nanoparticles are metal nanoparticles that can form coordination bonds with the PSS segments in PEDOT:PSS. The average particle size of the metal nanoparticles is 15-25 nm, and their polydispersity index (PDI) is less than or equal to 0.
25. The process of using a femtosecond laser to induce a two-photon polymerization reaction was carried out under the condition that the sample thickness was 8-12 μm. The femtosecond laser used had a wavelength of 500-600 nm, a pulse width of 100-300 fs, and a scanning speed of 5-50 μm / s. The composite photoresist uses ultrapure water as a solvent; the components of the composite photoresist include acrylate compounds as water-soluble polymer monomers, PEDOT:PSS as conductive basic filler, metal nanoparticles as conductive control filler, and photoinitiators with absorption peaks in the range of 250-320 nm. The pretreatment process for the substrate includes: first, cleaning the substrate with oxygen plasma, and then silanizing the cleaned substrate with a silane coupling agent containing functional groups that can react with the polymer monomers. The development process includes: sequentially immersing the three-dimensional micro / nano structure prototype in water and organic solvent in stages, followed by drying; The photoinitiator is Irgacure 2959, Irgacure 184, or Darocur 1173; The acrylate compound is polyethylene glycol diacrylate or trimethylolpropane triacrylate.